2012
DOI: 10.1038/nature11606
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 inhibition as a therapeutic strategy for lymphoma with EZH2-activating mutations

Abstract: In eukaryotes, post-translational modification of histones is critical for regulation of chromatin structure and gene expression. EZH2 is the catalytic subunit of the polycomb repressive complex 2 (PRC2) and is involved in repressing gene expression through methylation of histone H3 on lysine 27 (H3K27). EZH2 overexpression is implicated in tumorigenesis and correlates with poor prognosis in several tumour types. Additionally, somatic heterozygous mutations of Y641 and A677 residues within the catalytic SET do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
1,458
4
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,587 publications
(1,542 citation statements)
references
References 28 publications
57
1,458
4
4
Order By: Relevance
“…15,[19][20][21][22][23][24] Notably, its molecular or pharmacological inhibition leads to the reversal of the malignant phenotype. [24][25][26][27][28][29] Collectively, these findings demonstrate a role of EZH2 as a potential prognostic marker and therapeutic target in cancer. We and others have recently reported that (i) as compared with the normal myoblasts and muscle tissues EZH2 is markedly overexpressed in RMS 30,31 and (ii) EZH2 downregulation in vitro leads to myogenic-like differentiation of an embryonal RMS cell line.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…15,[19][20][21][22][23][24] Notably, its molecular or pharmacological inhibition leads to the reversal of the malignant phenotype. [24][25][26][27][28][29] Collectively, these findings demonstrate a role of EZH2 as a potential prognostic marker and therapeutic target in cancer. We and others have recently reported that (i) as compared with the normal myoblasts and muscle tissues EZH2 is markedly overexpressed in RMS 30,31 and (ii) EZH2 downregulation in vitro leads to myogenic-like differentiation of an embryonal RMS cell line.…”
Section: Introductionmentioning
confidence: 72%
“…26,27,29 In the attempt to evaluate the effect of pharmacologic inhibition of EZH2, we have used DZNep, which has been already shown to induce FBXO32 expression in cancer cells 25,28,40,66 in parallel with an EZH2 catalytic inhibitor, MC1945. 33,34 Both pharmacological treatments phenocopied the effects of genetic inhibition of EZH2 in vitro enhancing the apoptotic rate of fusion-positive alveolar RMS cells, upregulating FBXO32 and downregulating Myogenin.…”
Section: (Student's T-test) (B) Ezh2mentioning
confidence: 99%
“…Les molécules GSK126 et EI1 sont actives à la fois sur les deux formes d'EZH2. Elles inhibent de façon efficace la croissance de lignées cellulaires issues de lymphomes dans lesquelles la protéine EZH2 est mutée [41,42]. Une étude de phase I utilisant la molécule GSK126 a été lancée en avril 2014 chez des patients atteints de lymphomes B. Enfin, une autre étude clinique de phase I portant sur la molécule CPI-1205 dont la structure moléculaire n'a pas encore été dévoilée, a été initiée en 2015 chez des patients atteints de lymphomes B.…”
Section: Rôle Suppresseur De Tumeur D'ezh2unclassified
“…Several lines of evidence suggest that EZH2 deregulation is an important driver of cancer development and progression and that inactivation of EZH2 may be therapeutically effective in many cancers [4,5,11,12,73,[76][77][78][79][80][81][82][83][84][85][86][87][88][89] . EZH2 is highly expressed in a wide range of cancer types, including lung, breast, colon, prostate, bladder and pancreatic cancer, as well as sarcomas and lymphomas [4,5,11,12,76,77,80,82,83,[85][86][87][88] . Correspondingly, overexpression of EZH2 often correlates with advanced stages of human cancer progression and poor prognosis [4,12,76] .…”
Section: Prc2 and Diseasesmentioning
confidence: 99%
“…Since 2010, multiple cancer genome-wide studies have reveal ed that the function of the PRC2 complex and H3K27 methylation are widely associated with tumorigenesis [4,5,12,76,77] . Several lines of evidence suggest that EZH2 deregulation is an important driver of cancer development and progression and that inactivation of EZH2 may be therapeutically effective in many cancers [4,5,11,12,73,[76][77][78][79][80][81][82][83][84][85][86][87][88][89] .…”
Section: Prc2 and Diseasesmentioning
confidence: 99%